2016
DOI: 10.1016/j.ebiom.2016.05.037
|View full text |Cite|
|
Sign up to set email alerts
|

Serotonin Activates Bacterial Quorum Sensing and Enhances the Virulence of Pseudomonas aeruginosa in the Host

Abstract: Bacteria in humans play an important role in health and disease. Considerable emphasis has been placed in understanding the role of bacteria in host-microbiome interkingdom communication. Here we show that serotonin, responsible for mood in the brain and motility in the gut, can also act as a bacterial signaling molecule for pathogenic bacteria. Specifically, we found that serotonin acts as an interkingdom signaling molecule via quorum sensing and that it stimulates the production of bacterial virulence factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 30 publications
0
61
0
2
Order By: Relevance
“…This bacterial communication is necessary for biofilm formation, swarming motility, induction of gene expression, exopolysaccharide production, and the exchange of virulence factors (Sauer et al, ; Liu et al, ; Abraham, ). Therefore, high serotonin levels resulted in increased P. aeruginosa pathogenicity by enhancing biofilm formation and elaboration of virulence factors, in vitro (Knecht et al, ). In a mouse model, we observed that animals treated with exogenous serotonin and infected with P. aeruginosa exhibited an increase in intestinal bacterial load and mortality compared to untreated animals.…”
Section: Serotoninmentioning
confidence: 99%
See 1 more Smart Citation
“…This bacterial communication is necessary for biofilm formation, swarming motility, induction of gene expression, exopolysaccharide production, and the exchange of virulence factors (Sauer et al, ; Liu et al, ; Abraham, ). Therefore, high serotonin levels resulted in increased P. aeruginosa pathogenicity by enhancing biofilm formation and elaboration of virulence factors, in vitro (Knecht et al, ). In a mouse model, we observed that animals treated with exogenous serotonin and infected with P. aeruginosa exhibited an increase in intestinal bacterial load and mortality compared to untreated animals.…”
Section: Serotoninmentioning
confidence: 99%
“…Recent studies from our laboratory showed that increased levels of serotonin can enhance quorum sensing in Pseudomonas aeruginosa both in vitro and in vivo (Knecht et al, 2016). Quorum sensing is the process by which bacteria in close proximity are able to communicate with one another through chemical signaling (Castillo-Ju arez et al, 2015).…”
Section: Journal Of Cellular Physiologymentioning
confidence: 99%
“…Host factors can crosstalk with microbiota via QS [14] and trigger AHL- and PQS-dependent QS communication (Fig. 1), for example neurotransmitter serotonin, estrogen steroid, and stress hormones [15, 16]. …”
Section: Qs Signaling Network In P Aeruginosamentioning
confidence: 99%
“…Yet, in almost all organisms, elevated levels of 5-HT also signal stress (Chaouloff 2002;Chaouloff et al 1999;Deakin and Graeff 1991). Serotonin modulates quorum sensing and stimulates biofilm formation in Pseudomonas (Knecht et al 2016), a defense response of the bacterium, is synthesized and released upon exposure to abiotic stress in plants to promote abiotic stress tolerance (Erland et al 2016;Kaur et al 2015), promotes aversive behavior in C. elegans (Ooi and Prahlad 2017;Zhang et al 2005), and is released as one of the early responses to real or perceived threats by mammals (Chaouloff 2002;Chaouloff et al 1999;Deakin and Graeff 1991). Much of these contrary biological responses stimulated by 5-HT may have to do with the duration of exposure computed through feedback mechanisms that modulate the response of cells and animals to the presence of 5-HT at different timescales.…”
Section: ) (A) Vennmentioning
confidence: 99%